Hubungan Antar Umat Beragama (Studi Kritis Metodologi Penafsiran Tekstual) - Ahmad Taufik (Qur'an and Hadith Academic Society, 2014)
The textual interpretation of the Qur’an has been considered as the most valid and authoritative method in interpreting the Qur’an. However, this method has many weaknesses because it can produce intolerant and exclusive religious attitude. Therefore, an interpreter needs to consider not only the analysis of the text of the Qur’an but also its context of revelation. This statement is proven by analyzing the interpretation of Nasir al-Sa’di on inter religious relation. The data is first analyzed using the thematic approach. This approach is used to collect verses related to interreligious relation. In the next step, this interpretation is analyzed by contextual approach as proposed by Abdullah Saeed.